Beyond Wallace: a new lineage of Chrysorthenches (Lepidoptera: Yponomeutoidea: Glyphipterigidae) reveals a journey tracking its host-plants, Podocarpus (Pinopsida: Podocarpaceae). Issue 2 (10th March 2020) - Sohn, Jae-Cheon; Kobayashi, Shigeki; Yoshiyasu, Yutaka
Abstract: A northward trans-Wallacean radiation is demonstrated for Chrysorthenches, a member of the Orthenches group. Here we review Chrysorthenches and allied genera resulting in a generic transfer of Diathryptica callibrya to Chrysorthenches and two new congeners: C. muraseae Sohn & Kobayashi sp. nov. from Japan and C. smaragdina Sohn sp. nov. from Thailand. We review morphological characters of Chrysorthenches and allied genera, and find polyphyly of Diathryptica and the association of the Orthenches -group with Glyphipterigidae. These findings were supported in a maximum likelihood phylogeny of DNA barcodes from ten yponomeutoids. We analysed 30 morphological characters for 12 species of Chrysorthenches, plus one outgroup, via a cladistic approach. The resulting cladogram redefined two pre-existing Chrysorthenches species-groups and identified one novel lineage: the C. callibrya species-group. We review the host associations between Chrysorthenches and Podocarpaceae, based on mapping the working phylogenies. Our review suggests that ancestral Chrysorthenches colonized Podocarpus and later shifted to other podocarp genera. Biogeographical patterns of Chrysorthenches show that they evolved long after the Podocarpaceae radiation. Disjunctive trans-Wallacean distribution of the C. callibrya species-group is possibly related to the tracking of their host-plants and the complicated geological history of the island-arc system connecting Australia and East Asia.